Children’s perceptions of fathers’ contributions after parental separation - Lestari, A. Ayu Karyanci; Nurhayati, Siti Rohmah; Ummul, Putri Nur (Jurnal Ilmiah Psikologi Terapan, 2026)
Parental separation alters family dynamics and may affect children’s psychological well-being, particularly through changes in paternal involvement. While previous studies have largely focused on parental perspectives or childhood outcomes, limited attention has been given to how children in young adulthood perceive fathers’ contributions after divorce. This study aimed to explore young adults’ perceptions of fathers’ contributions following parental separation from emotional, relational, and financial perspectives. Using a qualitative exploratory-descriptive design, data were collected through semi-structured interviews with five young adult women aged 24–28 years. Participants were selected using purposive sampling with inclusion criteria: individuals who experienced parental divorce during childhood or adolescence, were currently in young adulthood, and were able to reflect on their emotional, social, and psychological experiences related to parental separation. Thematic analysis revealed five superordinate themes: emotional support, relationship with the father, psychological impact of parental separation, financial conditions, and expectations toward family relationships. Findings indicate that emotional presence and relational quality were perceived as more meaningful than financial contributions alone. This study highlights the importance of understanding post-divorce father involvement from children’s subjective perspectives and supports the development of post-separation parenting practices that prioritize emotional engagement.